Image-Based Analysis of Tumor Localization After Intra-Arterial Delivery of Technetium-99m-Labeled SPIO Using SPECT/CT and MRI. (24th January 2017) - Lee, In Joon; Park, Ji Yong; Kim, Young-il; Lee, Yun-Sang; Jeong, Jae Min; Kim, Jaeil; Kim, Euishin Edmund; Kang, Keon Wook; Lee, Dong Soo; Jeong, Seonji; Kim, Eun Jeong; Kim, Young Il; et al.
The aim of this study is to evaluate the localization of 99m Tc-labeled dextran-coated superparamagnetic iron oxide (SPIO) nanoparticles to the liver tumor using image-based analysis. We delivered 99m Tc-SPIO intravenously or intra-arterially (IA) with/without Lipiodol to compare the tumor localization by gamma scintigraphy, single-photon emission computed tomography (SPECT), and magnetic resonance imaging (MRI) in a rabbit liver tumor. The gamma and SPECT image-based analysis shows that the uptake ratio of the tumor to the normal liver parenchyma is highest after delivery of 99m Tc-SPIO with Lipiodol IA and that well correlates with the trend of the signal decrease in the liver MRIs. Intra-arterial delivery of SPIO with Lipiodol might be a good drug delivery system targeting the hepatic tumors, as confirmed by image-based analysis.